The complexity of the day-side X-line during southward interplanetary magnetic field - Burkholder, Brandon L.; Chen, Li-Jen; Sorathia, Kareem; Sciola, Anthony; Merkin, Slava; Trattner, Karlheinz J.; Gershman, Daniel; Ma, Xuanye; Connor, Hyunju (Frontiers in Astronomy and Space Sciences, 2023)
High-resolution global magnetohydrodynamics (MHD) simulations include both meso-and global-scale processes occurring at the magnetopause, which interact to determine the timedependent orientation of the day-side x-line (DXL). This study demonstrates that the global orientation of the DXL in GAMERA global MHD simulations varies on a time scale of minutes during steady southward interplanetary magnetic field conditions. This behavior manifests in observational data when reconnection outflows indicate that the direction to the x-line is opposite to the prediction from a steady-state model of the reconnection location. Because steady-state models of the DXL do not capture dynamics that are independent of solar wind variations, particularly surface waves and flux transfer events, they represent a time-averaged state of the system.